The Planning of the Jakarta – Cikampek II South Toll Gate - Usamah; Buana , Cahya (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
Toll roads have a significant impact on the movement of goods and services, but oftentimes toll roads, which are supposed to be barrier-free roads, do not serve their intended purpose. This is due to queue congestion at toll gates. This thesis discusses the "planning of Jakarta-Cikampek II South toll gate" using the Multi Channel Single Phase method as the basic structure for queuing processes with First In First Out (FIFO) queue discipline. In this thesis, toll gate planning is designed for the years 2020, 2025, and 2030, taking into account automatic toll booths and on-board toll booths. The result of the planning calculation for Jakarta-Cikampek II South toll gate in 2020 is that there are 5 ATG (Automatic Toll Gate) and 5 Exclusive ATGs for class I vehicles, and 1 On-Board Unit (OBU) toll booth for both entry and exit directions at Jati Asih toll gate. At Bantar Gebang toll gate, there are 8 ATG and 9 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Setu toll gate has 7 ATG and 8 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Sukaragam toll gate has 8 ATG and 9 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Taman Mekar toll gate has 8 ATG and 9 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Kutanegara toll gate has 6 ATG and 6 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Sadang toll gate has 2 ATG and 3 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. In 2025, Jati Asih toll gate has 6 ATG and 7 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Bantar Gebang toll gate has 9 ATG and 10 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Setu toll gate has 8 ATG and 9 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Sukaragam toll gate has 9 ATG and 10 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Taman Mekar toll gate has 9 ATG and 10 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Kutanegara toll gate has 7 ATG and 9 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Sadang toll gate has 3 ATG and 3 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. In 2030, Jati Asih toll gate has 6 ATG and 7 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Bantar Gebang toll gate has 10 ATG and 12 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Setu toll gate has 10 ATG and 11 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Sukaragam toll gate has 10 ATG and 12 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Taman Mekar toll gate has 10 ATG and 12 Exclusive ATGs for class I vehicles, and 1 OBU toll booth. Kutanegara toll gate has 7 regular toll booths, 9 special toll booths for class I vehicles, and 1 OBU toll booth. Sadang toll gate has 3 regular toll booths, 3 special toll booths for class I vehicles, and 1 OBU toll booth.